Critical Analysis of Advanced High-Grade Serous Epithelial Ovarian Cancer in Women: An Experience of 100 Cases from a Regional Cancer Center in Northeast India - Barmon, Debabrata; Patra, Sharda; Nandwani, Megha; Jethani, Roma; Kataki, A. C. (South Asian Journal of Cancer, 2023)
Ovarian cancer is the sixth most common cancer in women worldwide. Patients with ovarian carcinoma mostly present at an advanced stage with serous type of epithelial ovarian cancers, which is the most lethal of all pelvic malignancies. This study aims to critically analyze high-grade serous epithelial ovarian carcinomas in women from the Northeastern region of India and compare our data with Western literature to modify treatment strategies and improve survival outcomes. This hospital-based retrospective analysis involved data from the records of 100 women with high-grade epithelial ovarian cancer treated primarily with neoadjuvant chemotherapy followed by interval debulking surgery in the department of gynecologic oncology at a tertiary level regional cancer institute from January 2018 to December 2019. The demographic, clinical and pathological profile, and survival outcome were evaluated using descriptive statistics. The overall survival of the study population was calculated using Kaplan–Meier curves using SPSS software (version 24). The majority of women belonged to 41 to 55 years age group. At first presentation to the hospital, 89 and11% patients were in stage III and stage IV of disease, respectively. Clinically, 95% of women had ascites, and 18% had metastasis to lymph nodes. Distant metastasis to lungs and liver was present in 10 and 3% of cases, respectively. A substantial percentage (98%) of women had raised serum Ca125 > 1000 at baseline, ranging from 1,745 to 10,987 IU/mL. Almost two-thirds of the cases had partial-to-complete response to neoadjuvant chemotherapy (78%). In most of the women (72%), there was no residual disease at interval debulking surgery (R0), though 28% women had R1& R2 resection. The median overall survival time was 36 months. High-grade serous ovarian cancer is commonly seen in older age group, but its occurrence in younger population has also been observed. Early diagnosis is crucial in decreasing morbidity and mortality among these patients. Therefore, efforts should be made to identify risk factors for malignancy. Assessing each parameter of statistical information reflecting its own profile may be important for calculating the risk for the development of ovarian cancer, which can help in implementing preventive measures in the future.
Keywords: Ca125; epithelial ovarian cancer; interval debulking surgery; neoadjuvant chemotherapy; overall survival